Metformin Inhibits Lipoteichoic Acid–Induced Oxidative Stress and Inflammation Through AMPK/NRF2/NF-κB Signaling Pathway in Bovine Mammary Epithelial Cells - Arbab, Abdelaziz Adam Idriss; Lu, Xubin; Abdalla, Ismail Mohamed; Idris, Amer Adam; Chen, Zhi; Li, Mingxun; Mao, Yongjiang; Xu, Tianle; Yang, Zhangping (Frontiers in Veterinary Science, 2021)
The objective of this research was to explore the effect of metformin on the lipoteichoic acid (LTA)–induced mastitis model using isolated primary bovine mammary epithelial cells (PBMECs). The PBMECs were exposed to either 3 mM metformin for 12 h as a metformin group (MET) or 100 μg/mL LTA for 6 h as LTA group (LTA). Cells pretreated with 3 mM metformin for 12 h followed by washing and 100 μg/mL LTA exposure for 6 h served as the MET + LTA group. Phosphate-buffered saline was added to cells as the control group. PBMECs pretreated with different metformin doses were analyzed by a flow cytometry (annexin V–fluorescein isothiocyanate assay) to detect the cell apoptotic rate. We performed quantitative reverse transcriptase–polymerase chain reaction and Western blot analysis to evaluate the inflammatory and oxidative responses to metformin and LTA by measuring cellular cytotoxicity, mRNA expression, and protein expression. Immunofluorescence was used to evaluate nuclear localization. The results showed that the gene expression of COX2, IL-1β, and IL-6 significantly increased in the cells challenged with LTA doses compared to control cells. In inflammatory PBMECs, metformin attenuated LTA-induced expression of inflammatory genes nuclear factor κB (NF-κB) p65, tumor necrosis factor α, cyclooxygenase 2, and interleukin 1β, as well as the nuclear localization and phosphorylation of NF-κBp65 protein, but increased the transcription of nuclear factor erythroid 2–related factor 2 (Nrf2) and Nrf2-targeted antioxidative genes heme oxygenase-1 (HO-1) and Gpx1, as well as the nuclear localization of HO-1 protein. Importantly, metformin-induced activation of Nrf2 is AMP-activated protein kinase (AMPK)–dependent; as metformin-pretreated PBMECs activated AMPK signaling via the upregulation of phosphorylated AMPK levels, cell pretreatment with metformin also reversed the translocation of Nrf2 that was LTA inhibited. This convergence between AMPK and Nrf2 pathways is essential for the anti-inflammatory effect of metformin in LTA-stimulated PBMECs. Altogether, our results indicate that metformin exerts anti-inflammation and oxidative stress through regulation of AMPK/Nrf2/NF-κB signaling pathway, which highlights the role of AMPK as a potential therapeutic strategy for treatment of bovine mastitis.